KETERAMPILAN KEPEMIMPINAN BISNIS GLOBAL YANG EFEKTIF - Nazwirman Nazwirman (Direktorat Riset dan Pengabdian kepada Masyarakat Universitas Bina Darma, 2020)
This research is qualitative in nature that draws findings from various literatures in relation to global business leadership and cross-cultural management. This is an initial effort to identify the essence of leadership skills for global business leaders to face current and future challenges. In global business including technological innovation, and demographic change, companies must seek effective leadership for diverse organizational management. Leadership in global environmental conditions that seeks to involve cultural awareness, global mindset, effective interpersonal skills, and leader-employee relations and the need to develop leadership skills. There are eleven important skills identified for global business leaders that are effective in developing diverse locations. These skills are useful for growing employee potential, improving overall organizational performance, taking social responsibility, and cross-cultural human relations. So global business leaders need to continually update effective knowledge, skills and abilities in developing cross-cultural work and management environments, to be able to compete in the global market. Global business management and human resource development will be very useful by exploring empirically the essence of leader skills. In the future this strategy will be very beneficial for global business leadership practices.